Análisis de las propuestas caricaturísticas de Vilma Vargas: Humor y crítica en la sociedad actual - Naranjo Salvatierra, Kenya Isabel (2025)
This study examines Vilma Vargas' use of humor and social criticism in her comics, with special attention to the analysis of her creative style. Using a qualitative methodology and an exploratory design, the study aims to understand Vargas' comic recommendations and how they affect different contemporary situations. The graphic components that represent Vargas' artistic style, his communicational approaches and the political influence of his comics were determined through an exhaustive analysis of the literature on graphic humor and his comic proposals. The findings demonstrate that, by addressing contemporary social and political issues, Vilmatraca's cartoons significantly influence popular opinion. His sarcastic approach provokes public reflection by questioning significant facets of Ecuadorian society and governance. His work has received international attention despite obstacles such as censorship attempts, demonstrating his impact outside of Ecuador. Finally, he employs strategies such as visual irony and exaggerated facial and body language to engage audiences and convey important messages about corruption or flawed government processes. However, some cartoons may not be as well understood abroad, as they require a specialized understanding of regional issues or Ecuadorian political leaders.